Micromechanical characterisation of the influence of rhenium on the mechanical properties in nickel-base superalloys - Göken, Mathias; Durst, Karsten (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2004)
Three commercial single-crystalline nickel-base superalloys CMSX-6, CMSX-4 and CMSX-10 which have an increasing amount of rhenium and tungsten were investigated and the micromechanical properties such as hardness and modulus of elasticity of the individual phases were tested in a nanoindenting atomic force microscope. The hardness of the matrix phase increases with the concentration of refractory elements, whereas only a small change in the hardness of the precipitates was found. The hardness ratio of precipitate and matrix decreases significantly with increasing rhenium content in the initial condition and after heat treatment. In the initial condition the hardness ratio ranges from 1.31 for CMSX-10 to 1.41 for CMSX-4 and 1.67 for CMSX-6. Moreover, the modulus of elasticity increases with the concentration of refractory elements. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.microm
Keywords: Hardness; Modulus of elasticity; Nanoindentation; Nickel-base superalloy; Rhenium